Next generation of SiFAlin-based TATE derivatives for PET imaging of SSTR-positive tumors: influence of molecular design on in vitro SSTR binding and in vivo pharmacokinetics - Litau, Shanna; Niedermoser, Sabrina; Fricker, Gert; Wängler, Björn; Wängler, Carmen (Bioconjugate chemistry, 2015)
The Silicon-Fluoride-Acceptor (SiFA)-18F-labeling strategy has been shown before to enable the straightforward and efficient 18F-labeling of complex biologically active substances such as proteins and peptides. Especially in the case of peptides, the radiolabeling proceeds kit-like in short reaction times and without the need of complex product workup. SiFA-derivatized, 18F-labeled Tyr3-octreotate (TATE) derivatives demonstrated, besides strong somatostatin receptor (SSTR) binding, favorable in vivo pharmacokinetics as well as excellent tumor visualization by PET imaging. In this study, we intended to determine the influence of the underlying molecular design and used molecular scaffolds of SiFAlin-TATE derivatives on SSTR binding as well as on the in vivo pharmacokinetics of the resulting 18F-labeled peptides. For this purpose, new SiFAlin-(Asp)n-PEG1-TATE analogs (where n = 1-4) were synthesized, efficiently radiolabeled with 18F in a kit-like manner and obtained in radiochemical yields of 70-80%, radiochemical purities of ≥97%, and nonoptimized specific activities of 20.1-45.2 GBq/μmol within 20-25 min starting from 0.7-1.5 GBq of 18F. In the following, the radiotracer’s lipophilicities and stabilities in human serum were determined. Furthermore, the SSTR-specific binding affinities were evaluated by a competitive displacement assay on SSTR-positive AR42J cells. The obtained in vitro results support the assumption that aspartic acids are able to considerably increase the radiotracer’s hydrophilicity and that their number does not affect the SSTR binding potential of the TATE derivatives. The most promising tracer 18F-SiFAlin-Asp3-PEG1-TATE [18F]6 (LogD = −1.23 ± 0.03, IC50 = 20.7 ± 2.5 nM) was further evaluated in vivo in AR42J tumor-bearing nude mice via PET/CT imaging against the clinical gold standard 68Ga-DOTATATE as well as the previously developed SiFAlin-TATE derivative [18F]3. The results of these evaluations showed that [18F]6—although showing very similar chemical and in vitro properties to [18F]3—exhibits not only a slowed renal clearance compared to [18F]3, but also a higher absolute tumor uptake compared to 68Ga-DOTATATE, and furthermore enables excellent tumor visualization with high image resolution. These results emphasize the importance of systematic study of the influence of molecular design and applied structure elements of peptidic radiotracers, as these may considerably influence in vivo pharmacokinetics while not affecting other parameters such as radiochemistry, lipophilicity, serum stability, or receptor binding potential.